An Analysis of the Use of Audiovisual Media in Teaching Islamic Cultural History at Islamic Boarding Schools - Prima Kurnia, Sinto; Yumna, Yumna; Dahliana, Dina; Chairullah, Chairullah; Febriani, Afifah; Sufina Binti Saidi, Nuha (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
This study aims to analyze the influence of technology in the learning process of Islamic Religious Education in junior secondary schools. The main focus of this research is to observe the impact of using various technology-based teaching media, including slide presentations, audio videos, educational games and interactive quizzes, on students' understanding. The method used in this study is experimental quantitative research, where the researcher applies technology-based learning methods to evaluate their effect on learners' understanding of the teaching materials delivered by the teacher. The learning media used included laptops, projectors, and audio systems, as well as teaching materials in the form of videos and presentations. Data was collected from six six students involved in the study, with the results showing that about forty-two students or 65% of the total sample understood the material taught. This finding indicates that the use of technology in Islamic Education learning can have a positive impact on students' understanding.